STRATEGI PENINGKATAN EFEKTIVITAS PUSAT LOGISTIK BERIKAT MELALUI PENDEKATAN SWOT - Regina Astarini Soedarsono; Pradilla, Farchani Assih; ‘Aini, Kharisma Nurul; Ashari, Maulidya Yupika; Putra, I Dewa Gede Surya Uthama (JURNAL PERSPEKTIF BEA DAN CUKAI, 2025)
The Bonded Logistics Center (PLB) has been a strategic government policy since 2016 aimed at reducing logistics costs and accelerating dwelling time. Although it has shown positive impacts—such as improved delivery efficiency and reduced logistics expenses—Indonesia still faces significant national logistics challenges. The country’s logistics cost ratio stands at 23.5% of GDP, far higher than that of Malaysia and Singapore. Additionally, Indonesia's Logistics Performance Index (LPI) dropped from 46th in 2018 to 63rd out of 139 countries in 2023. This study aims to identify internal and external factors affecting PLB performance and to formulate efficiency enhancement strategies using SWOT analysis. The method employed is qualitative bibliometric analysis, focusing on regulations, infrastructure, facilities, and operational aspects of PLB. The results indicate that while PLB contributes to national logistics efficiency, further optimization is necessary. Recommended strategies include the utilization of AI and Big Data technologies, development of Cold Chain and Halal Logistics services, integration of the CEISA 4.0 system, and streamlining of cross-sector regulations. All proposed strategies align with the Strategic Plan of the Directorate General of Customs and Excise (DJBC) 2020–2024, which targets the strengthening of a digital-based logistics system and the positioning of PLB as a competitive regional distribution hub.